2011
DOI: 10.1177/0961463x10366081
|View full text |Cite
|
Sign up to set email alerts
|

Time perspective and autobiographical memory: Individual and gender differences in experiencing time and remembering the past

Abstract: This study examined the degree to which time perspectives were associated with the processes and content of autobiographical memory. A sample of 230 young adults (118 women) completed the Zimbardo Time Perspective Inventory (ZTPI; Zimbardo and Boyd, 1999 ), the Big Five Inventory (BFI; John and Srivastava, 1999 ), and responded in writing to seven memory prompts as well as to items from the Autobiographical Memory Questionnaire (AMQ; Rubin et al., 2003 ). The Past Positive and Future subscales of the ZTPI pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 48 publications
4
36
1
1
Order By: Relevance
“…For instance, autobiographical memory is an explicit form of memory previously shown to be influenced by TP (Ely & Mercurio, 2011) and cortisol levels (Schwabe & Wolf, 2010), respectively. As such, future studies could address the role of TP on the known interrelationships between memory, stress and emotion (Olivera-Figueroa, Marin, & Lupien, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, autobiographical memory is an explicit form of memory previously shown to be influenced by TP (Ely & Mercurio, 2011) and cortisol levels (Schwabe & Wolf, 2010), respectively. As such, future studies could address the role of TP on the known interrelationships between memory, stress and emotion (Olivera-Figueroa, Marin, & Lupien, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Because men tend to react more strongly in terms of physiological responses than women to laboratory-based psychosocial stress induction paradigms (Kudielka & Kirschbaum, 2005), and women tend to score higher than men on the Past Positive and Future TP tendencies (Ely & Mercurio, 2011; Zimbardo & Boyd, 1999), sex differences were assessed in preliminary analyses. Furthermore, menstrual cycle and oral contraceptive use were analyzed across women, since menstrual cycle and oral contraceptive use can confound cortisol (Kirschbaum, Kudielka, Gaab, Schommer, & Hellhammer, 1999; Wolfram, Bellingrath, & Kudielka, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…The Big Five Neuroticism and Extraversion dimensions also remained significant in the final equation. The incremental validity of the ZTPI over and above the Big Five traits has also been shown for health (Daugherty and Brase 2010), and for autobiographical memory for health (Ely and Mercurio 2011). …”
Section: Introductionmentioning
confidence: 85%
“…In particular, relationships between Past Negative and neuroticism, Present Hedonistic and extraversion, and Future and Conscientiousness are worth noting (Kairys & Liniauskaite, 2015). However, in spite of TP's moderate convergence with personality, a considerable number of studies have demonstrated the incremental validity of TPs over and above traditional (the Big Five traits) measures of personality (Daugherty and Brase (2010) for health; Ely and Mercurio (2011) for autobiographical memory; Zhang and Howell (2011) for well-being). Moreover, personality is a broad construct (not reducible to the Big Five), describing the coherency and consistency in an individual's pattern of affects, cognitions, desires and behaviors (Revelle, 2007).…”
Section: Intelligence and Non-cognitive Traitsmentioning
confidence: 95%